HISTORICAL INTERPRETATION OF LEGAL NORMS IN THE MODERN PERIOD OF SYSTEMATIC AXIOLOGICAL TRANSFORMATION - Serediuk, Vitalii (Scientific Journal of Polonia University, 2023)
The aim of the article is a theoretical and legal analysis of the historical interpretation of law in the context of doctrinal views, its justification and comparison with other theories. Achieving this goal involves: establishing the methodological value of the historical interpretation of law; show the need to follow a historical approach to the interpretation of law. The novelty of the article is to substantiate the practical value of the historical interpretation of law in the modern period of systemic axiological transformation and development of digital technologies. It is proposed to use the historical method of interpretation of legal norms in connection with digitized access to historical sources of law, in particular to the catalog and content of legal principles that were developed in different periods and continue to be the foundation of modern legal systems. The interpretive process gives the judge broad discretion. Voltaire’s fear would find expression in the judicial environment if the methods of interpretation of legal norms were weak, applied subjectively or simply exploited in order to achieve the desired goal. Then there would be a real possibility that in some cases the courts would usurp the functions of the legislature and call into question their own legitimacy. Only an accurate interpretation of the text of the law and its implementation in accordance with the intention and purpose of the legislator can regulate social relations and contribute to the development of society and the state. The analysis of the theory of historical interpretation of legal norms shows that the historical- critical analysis of law is interdisciplinary and relies on the growing amount of scientific literature as an approach to teaching and learning. It has been argued that historical approaches to the interpretation of legal norms are useful and effective for studying the relationship between internal and external contextuality in legal research. It is proved that due to the historical reconstruction of the genesis of the rule of law it is possible to explain the main factors, which probably explain the technical and legal features of legal interpretation. The formation of the rule of law in some way depends on socio-economic, political, cultural changes in society at a certain stage of its historical development. Which, in the end, affects our understanding of law and its epistemological consequences. Thus, for an adequate explication of the concept of legal technique of interpretation of legal norms, a relevant conceptual scheme that takes into account its characteristics is required.